PENGARUH KUALITAS ASET, LIKUIDITAS, RENTABILITAS, EFISIENSI OPERASIONAL, DAN SENSITIVITAS TERHADAP TINGKAT KECUKUPAN MODAL PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (Studi Kasus Pada Industri Perbankan periode tahun 2015-2017) - Ayu Giri Anjani; Jeni Susyanti; M. Agus Salim (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTThe purpose of this study is (1) to determine the effect of asset quality on the level of bank capital adequacy (2) to determine the effect of liquidity on the level of bank capital adequacy (3) to determine the effect of profitability on the level of bank capital adequacy (4) to determine the effect of operational efficiency on the level of bank capital adequacy (5) to determine the effect of sensitivity on the level of bank capital adequacy. The populations in this study are the banking industry listed on the Indonesia Stock Exchange in the period of 2015-2017 as many as 43 banking industries. Sampling technique using purposive sampling technique to obtain a sample of 13 banking industries. Data collection through questionnaire distribution. Data analysis in this research using SPSS version 21. Data analysis methods used in this study include normality test, multiple linear regression test, classic assumption test and hypothesis test.The result of this study indicate that asset quality has a negative and significant effect on the level of a bank capital adequacy, liquidity and operational efficiency have a positive and not significant effect on the level of bank capital adequacy. While profitability and sensitivity have a negative and not significants effect on the level of bank capital adequacy.Keywords: Asset Quality, Liquidity, Profitability, Operational Efficiency, Sensitivity, Capital Adecuacy Level.